Gaia unveils the kinematics of multiple stellar populations in 47 Tucanae. Issue 4 (18th July 2018) - Milone, A P; Marino, A F; Mastrobuono-Battisti, A; Lagioia, E P
ABSTRACT: The series of events, which occurred at high redshift and originated multiple stellar populations in Globular Clusters (GCs) are still poorly understood. Theoretical work suggests that the present-day dynamics of stars in nearby GCs, including the rotation and velocity dispersion, may retain important clues on the formation of multiple populations. So far, the dynamics of multiple populations have been investigated either from radial velocities of a relatively small sample of stars, or from relative proper motions of stars in the small field of view provided by the Hubble Space Telescope . In this context, Gaia provides the unique opportunity to investigate the dynamics of thousands of GC stars over a wide field of view. For the first time, we combine Gaia DR2 proper motions and multiband photometry to study the internal motions of the two main stellar populations of 47 Tucanae in a wide field of view. We confirm that this cluster exhibits high rotation on the plane of the sky and find that both stellar generations share similar rotation patterns. Second-generation stars show stronger anisotropies and smaller tangential-velocity dispersion than the first-generation stars, while there is no significant difference between their radial-velocity dispersion profiles. We discuss the impact of these results in the context of the formation scenarios for multiple stellar populations in GCs.